The rapid analysis of fungal growth in the presence of inhibitory effects - Williams, Tyson (Cranfield University, 2011)
For fungal contamination of foodstuffs, there are no fast, reliable, automated techniques to examine growth, nor have any predictive models been developed to describe the growth in the same way as for bacteria. Traditional plating methods can take 3 to 7 days to get adequate results depending on the fungal species utilised and well over a month for challenge testing, an unacceptable delay especially for the food industry. In this study two rapid analysis techniques were investigated, conductimetry (direct and indirect) and turbidimetry (Bioscreen), with the sole objective being to analyse their capability to detect fungal growth in optimum conditions and in the presence of inhibitory agents, in this case sorbic acid and vanillin. Three fungal (Aspergillus niger, Fusarium oxysporum and Pencillium verrucosum and one yeast species (Saccharomyces cerevisiae) were used, though only A. niger growth was analysed using both of the rapid analysis techniques. Two bacterial species (Escherichia coli and Salmonella enterica serovar typhimurium) were also tested using the conductimetry technique for comparison. It was found that both the impedance and turbidimetry methods provided a sensitive and rapid means of detecting, and, under standardised conditions, measuring the activity of micro-organisms. The rate of response showed close correlation with the concentration of both bacteria and spores in the initial inoculum for each strain tested so correlation curves could be constructed to estimate the number of viable cells and spores in a suspension. Moreover, both methods can be used for the accurate screening of potential antimicrobial substances. In comparison with the turbidimetry method though, the impedance method did show a greater deal of variability and there is the possibility it is unsuitable for the analysis of certain fungal species. In addition the direct impedance technique was found to be completely unusable for the analysis of fungal growth. Despite these disadvantages both are promising rapid alternatives to the standard plating technique.